Portfolio Assessment to Measuring Capabilities Communications and Collaborations Students - Rizal, M. Khairu Rizal; Dwi Yulianti; Handoko; Rosidin, Undang (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Assessments that can measure students' cognitive, affective and psychomotor abilities comprehensively are needed because assessments are currently only carried out at the end of learning and are only oriented to written tests and assignments. This study aims to produce a valid and effective portfolio assessment to measure the communication and collaboration skills of grade V elementary school students. This research is a type of Research and Development (R&D) research using the Borg & Gall model. The subjects of the study are material experts, linguists, and evaluation experts.  The methods used in data collection are observation, interviews, questionnaires and tests. Data collection instruments in the form of questionnaire sheets and tests. Data analysis techniques use qualitative, quantitative, and statistical inferential descriptive analysis. The results of the study, namely Portfolio Assessment, get valid and very practical qualifications. The results of the T-test show that there is a difference between the pretest and post-test results in students. It was concluded that portfolio assessment effectively improves students' communication and collaboration skills. The implication of this research is that the portfolio assessment developed can be used by teachers in learning.